The Correlation between Probiotic Consumption and Sleep Quality among Adults: A Systematic Review and Meta-Analysis - Pratiwi, Titis Ratih; Larasatie Nur Fibri, Dwi; Dwi Saputra, Wahyu (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2024)
This study aims to determine the relationship between probiotic consumption and an individual's sleep quality. A systematic search for relevant articles was conducted in Scopus, PubMed, Cochrane Library, and ScienceDirect databases for publication between 2013 and 2023. The article selection process is presented using a PRISMA diagram. Data analysis was performed using Review Manager Version 5.4 and publication bias was assessed using Comprehensive Meta-Analysis Software (CMA) V4. This systematic review and meta-analysis included 10 studies examining the effect of probiotic consumption on sleep quality measured by Pittsburgh Sleep Quality Index (PSQI) and 3 studies assessing the effect measured by Electroencephalogram (EEG). Based on the PSQI results, the findings indicate that probiotics considerably enhance sleep quality, with the pooled odds ratio of -0.32 (95% CI:-0.64–0.01; p=0.04). However, probiotic consumption shows no significant effect on sleep quality measured by EEG. Further studiesexploring the relationship between probiotic consumption and sleep quality using objective methods and larger samples are necessary to confirm the impact of probiotic supplementation on sleep quality. While these findings suggest that probiotic supplementation could be a potential strategy for improving sleep quality, additional research is required to strengthen these conclusions and investigate the underlying mechanisms.